Fatal myocardial infarction investigated using contrast‐enhanced postmortem computed tomography: A case report - Kohei Aoe; Yuichi Orita; Chikage Oshita; Shuji Date; Hiroki Teragawa (Clinical Case Reports, 2023)
Key Clinical Message Conventional autopsies are considered standard methods for clarifying cause of death. However, because of the increasing use of computed tomography, magnetic resonance imaging, and other diagnostic imaging techniques, autopsy imaging is now more frequently adopted to identify diseases with unknown causes and sudden deaths. A 84‐year‐old man was diagnosed with acute myocardial infarction using coronary angiography. After taking oral antiplatelet medication in the catheterization laboratory, the patient suddenly coughed violently, lost consciousness, and was diagnosed with cardiac arrest. Spontaneous circulation did not return after 50 min of cardiopulmonary resuscitation. To elucidate the cause of the cardiac arrest, we performed contrast‐enhanced postmortem computed tomography (PMCT), which revealed cardiac tamponade due to cardiac rupture of the inferior myocardium. Our findings reaffirm the effectiveness of contrast‐enhanced PMCT in the diagnosis of sudden death in the clinical setting.